Treatment of Complete Anal Stricture after Diverting Colostomy for Fournier’s Gangrene - Kenji Okumura; Tadao Kubota; Kazuhiro Nishida; Alan Kawarai Lefor; Ken Mizokami (Case Reports in Surgery)
Background. Anal stenosis is a rare but serious complication of anorectal surgery. Severe anal stenosis is a challenging condition. Case Presentation. A 70-year-old Japanese man presented with a ten-hour history of continuous anal pain due to incarcerated hemorrhoids. He had a history of reducible internal hemorrhoids and was followed for 10 years. He had a fever and nonreducible internal hemorrhoids surrounding necrotic soft tissues. He was diagnosed as Fournier’s gangrene and treated with debridement and diverting colostomy. He needed temporary continuous renal replacement therapy and was discharged on postoperative day 39. After four months, severe anal stenosis was found on physical examination, and total colonoscopy showed a complete anal stricture. The patient was brought to the operating room and underwent colostomy closure and anoplasty. He recovered without any complications. Conclusion. We present a first patient with a complete anal stricture after diverting colostomy treated with anoplasty and stoma closure. This case reminds us of the assessment of distal bowel conduit and might suggest that anoplasty might be considered in the success of the colostomy closure.